Economic Evaluation of Pesticide Use Externalities in the Cotton Zones of Punjab, Pakistan (The Pakistan Development Review, 2002)
At the inception of Pakistan in 1947, there was practically no plant protection service in the country and economic soundness of plant protection measures was not even realized for a long time. The use of chemicals as preventive measures to reduce losses by insects and diseases was almost non-existent during 1960s. However, the “grow more” pressure rendered the traditional methods insufficient, to control the ever increasing pest problem from 1970s onwards. Consumption of pesticides in Pakistan has increased from 665 metric tonnes (MT) in 1980 (when subsidy was withdrawn) to 69897 MT in 2002. This colossal increase in pesticide consumption has not led necessarily to an increase in the yield of crops, as demonstrated by Poswal and Williamson (1998) and Ahmad and Poswal (2000). This indiscriminate use of pesticides has destroyed the bio-control agents in the agro-ecosystems and the populations of natural enemies of the insects and pests have declined up to 90 percent during the last decade (of the past century) especially, in cotton growing areas of the country [Hasnain (1999)].